Cytotoxicity and bioactive potential of new root repair materials for use with BMP-2 transfected human osteoblast cells - Rodrigues, Elisandra Márcia [UNESP]; Viola, Kennia Scapin [UNESP]; Maldonado, Laura Gonzalez [UNESP]; Rossa-Junior, Carlos [UNESP]; Guerreiro-Tanomaru, Juliane Maria [UNESP]; Tanomaru-Filho, Mario [UNESP] (FapUNIFESP (SciELO), 2022)
Modified formulations of calcium silicate repair materials with additives have been developed to enhance handling, consistency, biocompatibility and bioactivity. Considering the relevance of osteoblastic cell response to mineralized tissue repair, human osteoblastic cells (Saos-2 cells overexpressing BMP-2) were exposed to mineral trioxide aggregate (MTA) (with calcium tungstate -CaWO4), MTA HP Repair, Bio-C Repair and Bio-C Pulpo. Cell viability was assessed by 3-(4,5-dimethylthiazol)-2,5-diphenyltetrazolium bromide (MTT) and neutral red (NR), and cell death, by flow cytometry. Gene expression of bone morphogenetic protein 2 (BMP-2), runt-related transcription factor 2 (RUNX-2), and alkaline phosphatase (ALP) osteogenic markers were evaluated by real-time polymerase chain reaction (RT-qPCR). ALP activity and alizarin red staining (ARS) were used to detect mineralization nodule deposition. Bioactive cements presented no cytotoxic effect, and did not induce apoptosis at the higher dilution (1:12). MTA, Bio-C Repair and Bio-C Pulpo exhibited higher ALP activity than the control group (P< 0.05) after 7 days. MTA, MTA HP and Bio-C Pulpo affected the formation of mineralized nodules (p < 0.05). Exposure to all cement extracts for 1 day increased BMP-2 gene expression. RUNX-2 mRNA was greater in MTA, MTA HP and Bio-C Repair. MTA, MTA HP and Bio-C Pulpo increased the ALP mRNA expression, compared with BMP-2 unexposed cells (p<0.05). Calcium silicate cements showed osteogenic potential and biocompatibility in Saos-2 cells transfected BMP-2, and increased the mRNA expression of BMP-2, RUNX-2, and ALP osteogenic markers in the BMP-2 transfected system, thereby promoting a cellular response to undertake the mineralized tissue repair.
Keywords: Biocompatible Materials; Bone Morphogenetic Protein 2; Cell Proliferation; Cell Survival; Endodontics